TINJAUAN HUKUM ISLAM TERHADAP PENETAPAN HADHANAH DALAM MENJAMIN KEBERLANGSUNGAN PENDIDIKAN ANAK DI PENGADILAN AGAMA MAKASAR KELAS IA - Andi Agung Mallongi Andi Muhammad Nasri; Musyfikah Ilyas; Muhammad Anis (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The subject of this research is the analysis of the judge's decision regarding the determination of hadhanah (custodial rights) in the Makassar Religious Court Class 1A with the object of research decision number 1850 Pdt.G/2014/PA.Mks. The main problem in this research consists of the main problem and 2 sub-problems, namely: 1) How does Islamic law review the imposition of hadhanah to ensure the continuity of children's education in the Makassar Religious Court Class IA? 2) How is the analysis of the judge's considerations in the 1850 Pdt.G/2014/PA.Mks decision in determining the burden of hadhanah in ensuring the continuity of children's education in the Makassar religious court class IA? The results of the research produced by the researcher show that the determination of hadhanah by the judge at least has indicators of considerations in determining it, namely; First, the state of health, whether the parent (father) is not disabled and does not have a mental disorder. Second, economic conditions, namely whether the parents (father) do not have large debts and have decent jobs that can meet the needs of their children (hadhanah). This is in line with the existence of Article 156 of the Compilation of Islamic Law (KHI) by looking at the abilities of parents. The implications of this research are: 1) The judge's decision must have clear concepts and methods so that justice seekers (justiciable) can accept and implement the judge's decision. So that judges must be required to have integrity, intellectuality and capability in carrying out their duties and responsibilities. This is necessary so that later the legal products it produces can then be in accordance with the value of the legal objectives, namely the existence of justice, expediency and certainty. Likewise with the case of determining hadhanah (Child Control) the judge must really be able to see the reality of the two parents, not only emphasizing mere positivism. 2) The public should not be too quick to draw a conclusion to the judge's decision which is always considered unfair and discriminatory. Because in resolving a case is not an easy thing, of course, through discussion, interpretation of views and considerations, then the judge can then decide on a case.